A comparative study of the local effect of tranexamic acid and phenylephrine on the amount of bleeding in rhinoplasty: A randomized clinical trial - Hooshang Akbari; Ebrahim Nasiri Formi; Abbas Alipour; Hamed Delam; Esmaeil Kavi; Negar Shahkarami (Babol University of Medical Sciences, 2024)
Background: Bleeding during nose surgery is very important, because it can cause a problem in the surgeon's field of view and lead to an increase in the probability of surgical complications. The aim of this study was to compare the local effects of tranexamic acid and phenylephrine on bleeding in rhinoplasty. Methods: The present study is a double-blind clinical trial in which 98 patients who were candidates for rhinoplasty Shiraz were randomly divided into 49 groups of phenylephrine and tranexamic acid. In the first group, 1 cc of phenylephrine and in the second group, 1 cc of tranexamic acid was used locally and then the variables in the two groups were compared. The current study was approved by the Iranian Clinical Trial Registration Center with code IRCT20201205049602N1. Results: The average blood pressure and heart rate in the phenylephrine group first increased and then decreased, but in the tranexamic acid group decreased from the beginning to 30 minutes. Based on the results of the test, there was a difference between the two groups in terms of the amount of bleeding, and a statistically significant relationship was observed. The average bleeding volume was lower in the phenylephrine group (p<0.0001). Conclusion: Results of this study showed that the amount of bleeding in the phenylephrine group was lower than that of tranexamic acid. It is recommended to use phenylephrine in rhinoplasty surgery to reduce bleeding and improve the surgeon's vision.